2021
DOI: 10.1111/jfpp.15254
|View full text |Cite
|
Sign up to set email alerts
|

Impact of winterization on fatty acids' composition, isomers, and oxidative stability of conjugated linoleic acids produced from selected vegetable oils

Abstract: Linoleic acid is an essential fatty acid containing 18 carbon atoms with two double bonds (Kaur et al., 2014). Vegetable oils, nuts, and seeds are regarded as a rich source of linoleic acids (LAs). Conjugated linoleic acids (CLAs) are used to describe a group of geometric and positional isomers of linoleic acid. In rumen, linoleic acid is converted to several isomers of CLA of cis and trans form. Isomers of CLA with trans double bond are biologically active and c-9, t-11 and t-10, c-12 have shown a great physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Monitored ripening effect on fatty acid composition of cheddar cheese, freshly prepared curd and 3 months old cheddar cheese had considerably different fatty acid profile. In this investigation, two isomers of conjugated linoleic acids were also found, concentrations of C18:2c9t13 and C18:2c9c12 in control were 0.91 and 2.11 mg/100 g. Intake of 2 g conjugated linoleic acid on daily basis can prevent obesity, cancer, diabetes and cardiovascular diseases ( Khan et al, 2021 ; Table 2 ).…”
Section: Resultsmentioning
confidence: 57%
“…Monitored ripening effect on fatty acid composition of cheddar cheese, freshly prepared curd and 3 months old cheddar cheese had considerably different fatty acid profile. In this investigation, two isomers of conjugated linoleic acids were also found, concentrations of C18:2c9t13 and C18:2c9c12 in control were 0.91 and 2.11 mg/100 g. Intake of 2 g conjugated linoleic acid on daily basis can prevent obesity, cancer, diabetes and cardiovascular diseases ( Khan et al, 2021 ; Table 2 ).…”
Section: Resultsmentioning
confidence: 57%
“…Concentrations of C18:3 in date seed oil, OF, and SOF were 1.87%, 3.62%, and 5.12%. Some commercial vegetable oils were fractionated/ winterized using dry fractionation technique, unsaturated fatty acids were intensified in low melting point fractions of all vegetable oils tested in the study (Khan et al, 2021). Fatty acid composition of various fractions of buffalo butter oil was considerably different from parent butter oil (Khan et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The induction period of date seed oil, OF, and SOF was 14.12, 10.78, and 9.16 h (Table 5). The induction period of OF and SOF was more than winterized sunflower, soybean, canola, cotton seed, and safflower oils (Khan et al, 2021). The higher induction period of OF and SOF of date seed oil was due to the presence of antioxidant substances in higher concentrations; further, the lower induction period of winterized sunflower, soybean, canola, cotton seed, and safflower oils was due to the loss of tocopherols and other antioxidant compounds during refining and bleaching, etc.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the change of LA to CLA is dependent on the concentration of LA. Safflower oil had more than 80% LA and yielded 31% CLA [6].…”
Section: Introductionmentioning
confidence: 99%